Peran Pembimbing Kemasyarakatan dalam rangka Mendukung Revitalisasi Penyelenggaraan Pemasyarakatan - Trisapto Agung Nugroho (Jurnal Ilmiah Kebijakan Hukum, 2020)
This research examined the revitalization of correctional administration, especially related to the role of probation officers. They have a strategic role in correction revitalization that is the pre-adjudication, adjudication and post-adjudication phases. The core business is community research, guidance, legal assistance, supervision, and a team of correctional observers. This research used a mix-method approach, namely, quantitative and qualitative. It consisted of primary data obtained from respondents with a google form questionnaire, a depth-interview with informants, and secondary data collected by books, journals, regulations, theory, and other literature. The results showed that the role had not optimized yet, It was influenced by some factors that were, a lack of the capacity, competence, and skills of the probation officers then, the ratio of the number of clients to the probation officers, budget support, facilities, and infrastructure to carry out the goals. Then the obstacles, namely the difference in perceptions of regulations/rules between correctional technical implementing units related to the duties and functions of probation officers, their skills, in terms of capacity, quantity, and quality to support the revitalization of correctional and lacking budget were factors that affected the optimization of their duties and functions.